The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1111/j.1365-2621.1989.tb05142.x
|View full text |Cite
|
Sign up to set email alerts
|

Chilling Injury in Cucumbers (Cucumis sativa L.) Associated with Lipid Peroxidation as Measured by Ethane Evolution

Abstract: The development of chilling injury in cucumbers stored at 4°C and 95% RH was evaluated. Irreversible damage due to chilling required 7 to 10 days as indicated by increases in tissue electrolyte leakage (from 30 to 70%), stress ethylene production (to 30-60 pMo1 g-l hr-r) and visual manifestations of injury. Low levels of ethane evolution (< 1 pMo1 g-l hr-') were observed for unchilled and continuously chilled fruits. Upon rewarming, ethane evolution was stimulated by an order of magnitude following a prior chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 27 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…Measurement of electrolyte leakage from plant tissues into a surrounding solution has long been used to evaluate the intactness and permeability of cell membranes (Murray and others 1989; Vasquez‐Tello and others 1990; Saltveit 2002). Numerous applications of this method have been made, including quantifying chilling injury in cucumbers (Kuo and Parkin 1989) and tomatoes (Saltveit 2002), mechanical damage to popcorn kernels (Goneli and others 2007) and tomatoes (Milczarek and others 2009), and high pressure and thermally treated onions (Gonzalez and others 2010b). In general, electrolytes will follow concentration gradients from a high concentration inside the cell to a lower concentration outside in the mannitol solution.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of electrolyte leakage from plant tissues into a surrounding solution has long been used to evaluate the intactness and permeability of cell membranes (Murray and others 1989; Vasquez‐Tello and others 1990; Saltveit 2002). Numerous applications of this method have been made, including quantifying chilling injury in cucumbers (Kuo and Parkin 1989) and tomatoes (Saltveit 2002), mechanical damage to popcorn kernels (Goneli and others 2007) and tomatoes (Milczarek and others 2009), and high pressure and thermally treated onions (Gonzalez and others 2010b). In general, electrolytes will follow concentration gradients from a high concentration inside the cell to a lower concentration outside in the mannitol solution.…”
Section: Resultsmentioning
confidence: 99%
“…Insoluble solids in alcohol were measured according to the method reported by Roe and Brummer (1981). Electrolyte leakage was evaluated following the method described by Kuo and Parkin (1989). Titratable acidity expressed as citric acid, was determined by direct titration with NaOH 0.1 N (AOAC 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, using ethane evolution as an indicator of linolenic acid oxidation, Kuo and Parkin reported that chilling injury in cucumbers stored at 4°C was paralleled by chilling-induced lipid oxidation. 67 Obviously, further work in this area is indicated. Taken together, these data allow a cautious con- elusion that the changes seen are consistent with the idea of chilling injury being a form of induced senescence.…”
Section: B Low-temperature Stressmentioning
confidence: 97%